The Perfectly Competitive Market A Pinnacle in the Development of the Laws of Classical Economics. - Golod, Igor (Cambridge Scholars Publisher, 2021)
Economics has two distinct faces, academic science and the real-world economy. If a university professor and an experienced business manager switched places one day, both would likely come to the disappointing conclusion that they barely understand each other's 'world'. This book serves to create a theoretical model of the economy that will be modern, simple, less prone to crises, and growing at a higher rate, made possible by the rapid development of computer technologies in recent decades.